Analisis Saham PT. Kalbe Farma, Tbk (KLBF) Bagi Calon Investor Periode 2025 - 2026 - Rifdatul Hanifah; Nur Hidayatillah; Mahardhika Harilinawan; Suparta, I Made (Nirta Learning Centre, 2025)
This study aims to analyze the performance of PT Kalbe Farma Tbk (KLBF) shares through fundamental and technical approaches during the period 2022 to 2024, as well as to prepare projections for 2025–2026. Fundamental analysis focuses on four main indicators, namely Earnings Per Share (EPS), Price to Earnings Ratio (PER), Return on Assets (ROA), and Return on Equity (ROE), which reflect profitability, efficiency, and stock valuation. Meanwhile, the technical analysis uses the Moving Average (MA), Moving Average Convergence Divergence (MACD), Relative Strenght Index (RSI), and support-resistance zone indicators to predict the direction of stock price movements. The results of the study show that KLBF shares have stable financial performance and positive technical signals, making them worthy of being accumulated in a medium to long-term portfolio. The price projection at the end of 2026 is in the range of IDR 2,000–IDR 2,200, with dividends that remain consistent. This study is expected to be a reference for prospective investors in developing rational and data-based investment strategies.